An Esterase‐like Lyase Catalyzes Acetate Elimination in Spirotetronate/Spirotetramate Biosynthesis. (21st January 2019) - Lees, Nicholas R.; Han, Li‐Chen; Byrne, Matthew J.; Davies, Jonathan A.; Parnell, Alice E.; Moreland, Pollyanna E. J.; Stach, James E. M.; van der Kamp, Marc W.; Willis, Christine L.; Race, Paul R.
Abstract: Spirotetronate and spirotetramate natural products include a multitude of compounds with potent antimicrobial and antitumor activities. Their biosynthesis incorporates many unusual biocatalytic steps, including regio‐ and stereo‐specific modifications, cyclizations promoted by Diels–Alderases, and acetylation‐elimination reactions. Here we focus on the acetate elimination catalyzed by AbyA5, implicated in the formation of the key Diels–Alder substrate to give the spirocyclic system of the antibiotic abyssomicin C. Using synthetic substrate analogues, it is shown that AbyA5 catalyzes stereospecific acetate elimination, establishing the ( R )‐tetronate acetate as a biosynthetic intermediate. The X‐ray crystal structure of AbyA5, the first of an acetate‐eliminating enzyme, reveals a deviant acetyl esterase fold. Molecular dynamics simulations and enzyme assays show the use of a His‐Ser dyad to catalyze either elimination or hydrolysis, via disparate mechanisms, under substrate control. Abstract : Eliminieren oder Hydrolysieren, das ist hier die Frage : Mechanistische, Struktur‐ und Computerstudien des Enzyms AbyA5 im Abyssomicin‐C‐Syntheseweg offenbaren den molekularen Ursprung der enzymkatalysierten Acetat‐Eliminierung. Das unerwartete Acetylesterase‐artige Grundgerüst des Proteins unterstützt sowohl die Acetat‐Eliminierung als auch die Ester‐Hydrolyse; welche Reaktion abläuft, wird durch die Art des Substrats bestimmt.